Local de realização do almoço de participantes da coorte de universidades mineiras (Estudo CUME): fatores associados e grau de processamento alimentar - Luisa Gazola Lage (2021)
Introduction: Food refers to both commensalism and to that which is eaten. Therefore, a meal can be influenced by several factors, such as socioeconomics, demographics, psychosocial, political, and cultural aspects, among others. Lunch is the Brazilian’s main meal and represents an average of 41% of the total energy consumed during the day. Therefore, the place where this meal is held and one’s lifestyle can positively or negatively influence the quality of diet and the health of individuals. Objective: To analyze factors associated with the location of lunch and the degree of food processing in participants of the Cohort of Universities of Minas Gerais (CUME Study). Method: This is a descriptive and analytical cross-sectional study developed with the CUME’s baseline data. The outcome variable of this work was the place where lunch was held, recoded as: “exclusively at home”, “mixed (at home and away from home)” and “exclusively away from home”. The sample was characterized by means of absolute and relative frequency distributions, and bivariate and multivariate (multinomial logistic regression) analyses of association between the explanatory variables and the outcome variable were also performed. The level of statistical significance set was 5%. Results: From a total of 6,892 participants, 52.8% reported having lunch in a mixed environment, while 21.3% and 25.9% reported having lunch exclusively at home and away from home, respectively. In comparison with home environment, it was observed that the following characteristics significantly reduced the chance of having lunch in a mixed environment: female gender; ages between 40 and 49 years; being retired, homeless or unemployed; live with more people in the household. On the other hand, the following characteristics significantly increased the chance of having lunch in a mixed environment: being a student; having higher family income and having the habit of binge drinking. Similar patterns of associations were also found for participants who reported eating lunch exclusively outside the home, with the addition that having four or more meals a day significantly reduced the chance of occurrence of this outcome. Regarding the NOVA classification, it was found that individuals who ate exclusively at their home environment had a higher consumption of minimally processed food and culinary ingredients (MPF/CI) and lower consumption of ultra-processed food when compared to the other categories. Conclusion: The consumption of lunch in a mixed environment or exclusively away from home was more frequent in male individuals, students or workers, with higher family income, with the habit of binge drinking, and was associated with higher consumption of ultra-processed foods. Having lunch exclusively at home favored an improvement in the quality of the diet.